Solid dispersions based on chitosan/hypromellose phthalate blends to modulate pharmaceutical properties of zidovudine - Pedreiro, Liliane Neves [UNESP]; Boni, Fernanda Isadora [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP]; Ferreira, Natália Noronha [UNESP]; Gremião, Maria Palmira Daflon [UNESP] (Taylor & Francis, 2022)
Zidovudine (AZT) has been widely used alone or in combination with other antiretroviral drugs for the treatment of human immunodeficiency virus. Its erratic oral bioavailability necessitates frequent administration of high doses, resulting in severe side effects. In this study, the design of mucoadhesive solid dispersions (SDs) based on chitosan (CS) and hypromellose phthalate (HP) was rationalized as a potential approach to modulate AZT physicochemical and pharmaceutical properties. SDs were prepared at different drug:polymer ratios, using an eco-friendly technique, which avoids the use of organic solvents. Particles with diameter from 56 to 73 µm and negative zeta potentials (–27 to −32 mV) were successfully prepared, achieving high drug content. Infrared spectroscopy revealed interactions between polymers but no interactions between the polymers and AZT. Calorimetry and X-ray diffraction analyses showed that AZT was amorphized into the SDs. The mucoadhesive properties of SDs were evidenced, and the control of AZT release rates from the matrix was achieved, mainly in acid media. The simple, low-cost, and scalable technology proposed for production of SDs as a carrier platform for AZT is an innovative approach, and it proved to be a feasible strategy for modulation the physico-chemical, mucoadhesive, and release properties of the drug.
Keywords: chitosan; controlled release; mucoadhesion; oral delivery; Solid dispersion